TECHNOLOGICAL THEORY OF MONEY AND THE SCIENCE OF MONEY IN THE CONDITIONS OF THE 9TH TECHNOLOGICAL ORDER - Glushchenko, Valery Vladimirovich (International Journal of Research -GRANTHAALAYAH, 2022)
The subject of the article is the technological theory of money as a methodological basis for the development of the global monetary system; the object of the article is the monetary system in the conditions of the 9th technological order; the purpose of the article is to reduce risks in the development of the global monetary system during the ninth technological order; to achieve this goal, the following tasks are solved: historical analysis of the development of forms and types of money; development of the technological theory of money; description of the monetary innovation multiplier and its significance in the monetary system; the scientific methods of this article are: historical and system analysis; theory of technological orders; theory of money; heuristic synthesis; comparative analysis; scientific novelty consists in the formation of the technological theory of money as the methodological basis of the post-industrial monetary system.